Wódz, naród, rasa. Ideologiczne przesłanki nazistowskich koncepcji prawa - Maciejewski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The subject matter of the article is devoted to discussing the ideological premises of the content, aims, and functions of Nazi law from the perspective of the legal theoreticians and practitioners of the Third Reich. Firstly, the significance and role of the supreme leader the Führer of the National Socialists and Germany in asingle person, namely Adolf Hitler, is discussed. The legal doctrine of the Nazi state perceived him — just as he did himself — to be the basic source of law and treated his political decisions as such. In fact, these decisions were even thought to stand above the Weimar Constitution of 1919 which was only formally in force and other pieces of legislation. Hitler was not merely viewed as the supreme legislator, but also as the highest judge, acting by the will of the German nation. Judicial decisions in the Third Reich were issued on his behalf. According to Nazi lawyers, Hitler as Führer embodied and articulated the will of the German nation, whose needs, interests, and aspirations were considered the purpose behind the functioning of the state and the Reich’s law. Furthermore, the German national community deutsche Volksgemeinaschaft rose to the rank of the near absolute determinant of the law’s form and content. It was, in fact, the reference for one of the important principles of Nazi law, i.e. the common good before personal good Gemeinnutz vor Eigennutz — hence, anegation of the concepts of individualism, including the unchallengeable nature of private property. In addition, the ideological premises of the Nazi concept of law also comprised racial issues. The Third Reich placed particular emphasis on racial purity and hygiene — which referred predominantly to the Germanic race — as acondition for the German national community’s healthy functioning. Nazi law, inter alia, was supposed to serve precisely that end. The legal doctrine in Germany at the time adopted the unequivocal position that the law — together with the administration of justice — should be one of the most important guards of the longevity and purity of the Germanic race sometimes referred to as the Aryan race. This stipulation, which for the most part was consistently implemented, was closely linked to the National Socialists’ almost zoological antisemitism. It was reflected in numerous normative acts by the Third Reich’s authorities targeting the Jewish population in Germany and the countries it occupied during WWII.
Keywords: prawo; narodowy socjalizm; lider; naród; rasa ludzka; Trzecia Rzesza